(untitled) (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2018)
Character education is essentially a virtue value education that aims to shape the character of students so that they are dignified and noble. Islamic boarding schools are a national education subsystem that has been developing for along time and has proven successful in educating santri to have noble character. The success of Islamic boarding schol in educating their santri characters because Islamic boarding schools have a number of character values instilled in their students by using strategies and methods comprehensively. This study examines the value of character education in Bahrul Ulum Islamic boarding school in Tambakberas Jombang. This study uses a qualitative approach that aims to describe the subject of research phenomenologically. The results of this study are that the values of character education instilled in Bahrul Ulum Islamic boarding school are 10 items, namely: faithful, honesty, sincerity, obedience and respect, simplicity, brotherhood independence, love in science, freedom and leadership. These character of values are a yardstick for the goodness of someone who must be manifested in the mind, attitude and behavior in relation to God, itself, family, society, nation people, and natural environment.